2018
DOI: 10.1097/ccm.0000000000003092
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes in Patients with Vasodilatory Shock and Renal Replacement Therapy Treated with Intravenous Angiotensin II

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(150 citation statements)
references
References 39 publications
7
140
0
3
Order By: Relevance
“…Although surprising, these findings may be valid given that larger animals better mimic the human cardiovascular response in sepsis 90100101102. More specifically, ovine autoregulatory responses in untreated shock and shock treated with vasoactive drugs are similar to those in human kidneys with AKI 100101103. Increased investigation of the interplay of the inflammatory cytokines and infiltrating cells and apoptosis will further our knowledge on the effect of these factors on the renal histology and the macrocirculation and microcirculation.…”
Section: Pathobiology Of Sa-akimentioning
confidence: 91%
See 2 more Smart Citations
“…Although surprising, these findings may be valid given that larger animals better mimic the human cardiovascular response in sepsis 90100101102. More specifically, ovine autoregulatory responses in untreated shock and shock treated with vasoactive drugs are similar to those in human kidneys with AKI 100101103. Increased investigation of the interplay of the inflammatory cytokines and infiltrating cells and apoptosis will further our knowledge on the effect of these factors on the renal histology and the macrocirculation and microcirculation.…”
Section: Pathobiology Of Sa-akimentioning
confidence: 91%
“…The selection of the ideal vasopressor in the setting of shock (regardless of AKI status) has been the source of several large scale multicenter trials 103131132133134135. In the setting of SA-AKI, traditional agents such as norepinephrine (noradrenaline), epinephrine, vasopressin, and dopamine, as well as more novel agents such as angiotensin II and levosimendan, have been investigated.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the kidney effects are unclear in patients with vasodilatory shock treated with angiotensin II because of inconsistent, albeit not statistically significant, findings in ATHOS‐3 on incidences of AKI (lower with angiotensin II), creatinine increase more than 50% (higher with angiotensin II), and initiation of dialysis (higher with angiotensin II) . Interestingly, a post hoc analysis of ATHOS‐3 found lower short‐term mortality in patients with established AKI treated with renal replacement therapy at baseline who were randomized to angiotensin II . Together, these data show that angiotensin II has multiple and varied effects on vascular beds that may lead to organ‐specific ADRs for which clinicians must monitor.…”
Section: Adrs Of Angiotensin II and Risk Mitigationmentioning
confidence: 98%
“…The investigators showed a significant decrease in the incidence of postoperative AKI when the KDIGO bundle was implemented. More recently, angiotensin II, a newly approved drug for septic or distributive shock (ATHOS-3 trial) [103], showed improved liberation from RRT at day 7 in a post hoc analysis of AKI patients [104]. These findings open an interesting prospect for further research focusing on AKI recovery in critically ill patients with shock that require RRT.…”
Section: Acute Kidney Injury and Critical Care Nephrologymentioning
confidence: 99%